Encyclopedia Interrupta, or Gale’s Unfinished: the Scandal of the EJ2 - Walfish, Barry (Judaica Librarianship, 2011)
Encyclopedias are important reference works. They are meant to summarize the state of knowledge in any given field and convey it to both the layperson and the scholar in a clear, concise manner. For Jews and Judaism, the first major effort in this regard was the Jewish Encyclopedia of 1906, which drew upon the knowledge of a cadre of European and American scholars of the Science of Judaism (Wissenschaft des Judentums). Its successor the German Encyclopaedia Judaica began to appear in 1929 but was interrupted in 1934 by the rise of Nazism. It had only reached the end of the letter L. After the war, efforts resumed which resulted in the production of two major encyclopedias, The Hebrew Encyclopaedia Hebraica (ha-Entsiklopedyah ha-‘Ivrit), completed in 1982, and the English Encyclopaedia Judaica (henceforth EJ1), which first appeared in 1971 followed by a corrected edition in 1972. Both works were published in Israel and are considered to be major achievements. The latter used a lot of material from both its German and Hebrew predecessors.